2021
DOI: 10.3892/etm.2021.9857
|View full text |Cite
|
Sign up to set email alerts
|

Underlying mechanisms of the effect of minocycline against Candida albicans biofilms

Abstract: Minocycline (MH) is a broad-spectrum antimicrobial agent and semisynthetic tetracycline derivative, which has been widely used in the clinic due to its efficacy. Having the strongest anti-microbial effect, MH exceeded the traditional scope of antibiotics and its previously unknown antifungal activity is also gradually being discovered. To preliminarily investigate the inhibitory effect of MH on Candida albicans ( C. albicans ), changes of cell growth, hyphal format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Furthermore, the use of broad-spectrum antibiotics has been linked to the emergence of Candida-resistant strains which might cause life-threatening bloodstream infection in susceptible patients [78]. Similar findings have been reported with doxycycline and minocycline [35].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the use of broad-spectrum antibiotics has been linked to the emergence of Candida-resistant strains which might cause life-threatening bloodstream infection in susceptible patients [78]. Similar findings have been reported with doxycycline and minocycline [35].…”
Section: Discussionsupporting
confidence: 59%
“…The aim of this study was to evaluate the effect of sarecycline compared to minocycline on representative microbiota (both bacteria and fungi) commonly found in the human gastrointestinal tract using an in-vitro approach. Importantly, although antibiotics are known to have minimal impact on fungi, our data showed that minocycline have inhibitory activity against Candida [35]. Based on this, we include 4 different Candida species in our study comparing minocycline and sarecycline.…”
Section: Introductionmentioning
confidence: 99%